The hazards of gastric lavage for intentional self-poisoning in a resource poor location - Eddleston, M.; Haggalla, S.; Reginald, K.; Sudarshan, K.; Senthilkumaran, M.; Karalliedde, L.; Ariaratnam, C. A.; Sheriff, M.H.R.; Warrell, D.A.; Buckley, N.A. (Taylor & Francis, 2007)
The 10–20% case fatality found with self-poisoning in the developing world differs markedly from the 0.5% found in the West. This may explain in part why the recent movement away from the use of gastric lavage in the West has not been followed in the developing world. After noting probable harm from gastric lavage in Sri Lanka, we performed an observational study to determine how lavage is routinely performed and the frequency of complications. Case series. Fourteen consecutive gastric lavages were observed in four hospitals. Lavage was given to patients unable or unwilling to undergo forced emesis, regardless of whether they gave consent or the time elapsed since ingestion. It was also given to patients who had taken non-lethal ingestions. The airway was rarely protected in patients with reduced consciousness, large volumes of fluid were given for each cycle (200 to more than 1000 ml), and monitoring was not used. Serious complications likely to be due to the lavage were observed, including cardiac arrest and probable aspiration of fluid. Health care workers perceived lavage as being highly effective and often life-saving; there was peer and relative pressure to perform lavage in self-poisoned patients. Conclusions. Gastric lavage as performed for highly toxic poisons in a resource-poor location is hazardous. In the absence of evidence for patient benefit from lavage, (and in agreement with some local guidelines), we believe that lavage should be considered for few patients – in those who have recently taken a potentially fatal dose of a poison, and who either give their verbal consent for the procedure or are sedated and intubated. Ideally, a randomized controlled trial should be performed to determine the balance of risks and benefits of safely performed gastric lavage in this patient population.
Clinical Toxicology: 2007; 45; 136-143p.
Keywords: Self-poisoning; Gastric lavage; Pesticides